Macro and Microscope Aspects in the 5-FU-Induced Oral Mucosistis in Model - Moreira Fonseca, Khetyma; Freire Carvalho, Neilton; Rolim Medeiros , Jand Venes (Brazilian Journal of Case Reports, 2021)
Not applicable.